2013
DOI: 10.1007/s00429-013-0510-1
|View full text |Cite
|
Sign up to set email alerts
|

Action-verb processing in Parkinson’s disease: new pathways for motor–language coupling

Abstract: Recent studies suggest that action-verb processing is particularly affected in early stage Parkinson's disease (PD), highlighting the potential role of subcortical areas in language processing and in the semantic integration of actions. However, this disorder-related language impairment is frequently unrecognized by clinicians and often remains untreated. Early detection of action-language processing deficits could be critical for diagnosing and developing treatment strategies for PD. In this article, we revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
102
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 118 publications
(133 citation statements)
references
References 136 publications
11
102
0
4
Order By: Relevance
“…Unlike the other Indo-European languages considered, Chinese lacks explicit word-class contrasts in its grammatical morphology, which suggests that neural noun-verb dissociations may be influenced by structural properties of the individual's native language. [57,58] (for further discussion of the model, see [48,59] [13,15], amyotrophic lateral sclerosis [14,60], corticobasal degeneration [61,62], and frontotemporal dementia [63,64]. This evidence A classic ACE (compatible facilitation and incompatible delay of RTs) was observed for controls, but no ACE was observed in early PD participants.…”
Section: Action-language Impairments In Parkinson's Diseasementioning
confidence: 94%
See 1 more Smart Citation
“…Unlike the other Indo-European languages considered, Chinese lacks explicit word-class contrasts in its grammatical morphology, which suggests that neural noun-verb dissociations may be influenced by structural properties of the individual's native language. [57,58] (for further discussion of the model, see [48,59] [13,15], amyotrophic lateral sclerosis [14,60], corticobasal degeneration [61,62], and frontotemporal dementia [63,64]. This evidence A classic ACE (compatible facilitation and incompatible delay of RTs) was observed for controls, but no ACE was observed in early PD participants.…”
Section: Action-language Impairments In Parkinson's Diseasementioning
confidence: 94%
“…The temporal lobe, the basal ganglia, and the thalamus (temporal-basal ganglia-thalamocortical component) comprise loops that would play a central role in the grounding of abstract conceptual knowledge involved in words referring to motor concepts. Modified with permission from [59].…”
Section: Action-language Impairments In Parkinson's Diseasementioning
confidence: 99%
“…For example, Cardona et al (2013) and Ibáñez et al (2013) postulate that action-verb processing and motor-language coupling depend on a network involving loops from cortical areas to BG/thalamic structures and back to the cortex. Hence, BG affectation in early PD would lead to the selective disruption of this language domain.…”
Section: Introductionmentioning
confidence: 99%
“…The motor theory of language based on the Embodied Cognitive Theory suggests that action-related language is located in the areas of the brain related with action. Indeed, the activation of the primary motor and premotor cortex while processing words or sentences that describe action including movement of the mouth, hand or leg supports this theory (4). In contrast, there are also studies showing that activation of cortical motor areas that have somatotopic organization with action-related language does not follow somatotopic organization (6).…”
Section: Introductionmentioning
confidence: 98%
“…These disturbances include morphosyntactic, lexicalsemantic, and discourse-level processes. Studies show disturbances in language functions including understanding long and complex sentences, action word recognition, action word naming and producing, and metaphor comprehension (4). Although some of these disturbances are associated with impairment in cognitive processes including executive functions, working memory, and selective attention, some studies showed that language disturbances were independent from cognitive decline (4).…”
Section: Introductionmentioning
confidence: 99%